Chronic Effects of Breaching Blast Exposure on Sensory Organization and Postural Limits of Stability. Issue 11 (November 2021) - Haran, F.J.; Zampieri, Cris; Wassermann, Eric M.; Polejaeva, Elena; Dell, Kristine C.; LoPresti, Matthew L.; Stone, James R.; Ahlers, Stephen T.; Carr, Walter
Abstract : Objective: The goal of this effort to investigate if experienced breachers, professionals with a career history of exposure to repeated low-level blasts, exhibited postural instability. Methods: Postural data were examined using traditional tests of means and compared to normative data. Results: Breachers had significantly lower NeuroCom Sensory Organization Test (SOT) visual scores (within normative limits), prolonged Limits of Stability (LOS) test reaction time (30% of breachers and 7% of controls testing abnormal), and slower LOS movement velocity (21% of breachers and 0% of controls testing abnormal) compared to controls. Conclusion: Our LOS test findings are like those previously reported for students in the military breacher training course and seem to indicate that while acute effects of blasts on sensory control of balance fade away, effects on postural LOS persist over time.